Electromagnetic wave propagation in the surface-ionosphere cavity of Venus - Simões, F; Hamelin, M; Grard, R; Aplin, K; Béghin, C; Berthelier, J; Besser, B; Lebreton, J; López-Moreno, J; Molina-Cuberos, G; Schwingenschuh, K; Tokano, T (2008)
The propagation of extremely low frequency (ELF) waves in the Earth surface-ionosphere cavity and the properties of the related Schumann resonances have been extensively studied in order to explain their relation with atmospheric electric phenomena. A similar approach can be used to understand the electric environment of Venus and, more importantly, search for the evidence of possible atmospheric lightning activity, which remains a controversial issue. We revisit the available models for ELF propagation in the cavity of Venus, recapitulate the similarities and differences with other planets, and present a full wave propagation finite element model with improved parameterization. The new model introduces corrections for refraction phenomena in the atmosphere; it takes into account the day-night asymmetry of the cavity and calculates the resulting eigenfrequency line splitting. The analytical and numerical approaches are validated against the very low frequency electric field data collected by Venera 11 and 12 during their descents through the atmosphere of Venus. Instrumentation suitable for the measurement of ELF waves in planetary atmospheres is briefly addressed. Copyright 2008 by the American Geophysical Union.